A Best-worst Scaling Usage in Marketing Research - Oláh, Bertold (International Journal of Engineering and Management Sciences, 2022)
Best-worst scaling (BWS) is a method of data collection and / or a theory of how respondents give the first and worst rankings in a list. In my article, I look at what best-worst scaling (BWS) is, what areas it is used to, and what the method itself is. I then turn to the BWS method, within which I examine its element: the BWS object case (case 1), the BWS profile case (case 2), and the BWS multi-profile case (case 3). I will detail the use of BWS in marketing research, and then compare the Likert-scaling method and BWS. I summarize my conclusions at the end of my article.